Caveolin-1 is involved in fatty infiltration and bone-tendon healing of rotator cuff tear - Shanhong Fang; Mengqiang You; Jie Wei; Peng Chen (BMC, 2023)
Abstract Background Caveolin-1 has been predicted, based on RNA transcriptome sequencing, as a key gene in rotator cuff tear (RCT) and it is related to fatty infiltration. This study aims to elucidate the upstream and downstream mechanism of Caveolin-1 in fatty infiltration and bone-tendon healing after RCT in rat models. Methods Differentially expressed genes related to RCT were screened, followed by functional enrichment analysis and protein-protein interaction analysis. GATA6 was overexpressed and Caveolin-1 was knocked down in tendon stem cells (TSCs) to evaluate their effects on the adipogenic differentiation of TSCs. In addition, a RCT rat model was constructed and injected with lentivirus carrying oe-GATA6, oe-Caveolin-1 alone or in combination to assess their roles in fatty infiltration and bone-tendon healing. Results and conclusion Caveolin-1 was identified as a key gene involved in the RCT process. In vitro results demonstrated that Caveolin-1 knockdown inhibited adipogenic differentiation of TSCs by activating the cAMP/PKA pathway. GATA6 inhibited the transcription of Caveolin-1 and inhibited its expression, thus suppressing the adipogenic differentiation of TSCs. In vivo data confirmed that GATA6 overexpression activated the cAMP/PKA pathway by downregulating Caveolin-1 and consequently repressed fatty infiltration, promoted bone-tendon healing, improved biomechanical properties and reduced the rupture risk of injured tendon in rats after RCT. Overall, this study provides novel insights into the mechanistic action of Caveolin-1 in the fatty infiltration and bone-tendon healing after RCT.